2018
DOI: 10.1126/science.aar2231
|View full text |Cite
|
Sign up to set email alerts
|

Risk-based reboot for global lab biosafety

Abstract: New WHO guidance could expand access to lab facilities

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 2 publications
0
12
0
8
Order By: Relevance
“…While both Orientia spp or R. typhi can cause serious infections, it is difficult to maintain a strong argument for their classification as RG3 organisms, as they are treatable with antibiotics and do not spread in the community by person-to-person contact. To further compound biosafety restrictions on Orientia spp or R. typhi laboratory investigations, the mistaken belief that risk group is equal with biosafety level (BSL) [55] has resulted in the erroneous requirement of BSL-3 for Orientia spp or R. typhi work while not considering the risk associated with the individual procedures. BSL-3 containment laboratories fundamentally differ from BSL-2 laboratories in that they provide protection to the outside environment from accidental aerosol contamination but no additional user protection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While both Orientia spp or R. typhi can cause serious infections, it is difficult to maintain a strong argument for their classification as RG3 organisms, as they are treatable with antibiotics and do not spread in the community by person-to-person contact. To further compound biosafety restrictions on Orientia spp or R. typhi laboratory investigations, the mistaken belief that risk group is equal with biosafety level (BSL) [55] has resulted in the erroneous requirement of BSL-3 for Orientia spp or R. typhi work while not considering the risk associated with the individual procedures. BSL-3 containment laboratories fundamentally differ from BSL-2 laboratories in that they provide protection to the outside environment from accidental aerosol contamination but no additional user protection.…”
Section: Discussionmentioning
confidence: 99%
“…At present, the most extensive guidance is provided by the US government [52], which states that BSL-2 practices, containment equipment, and facilities are recommended for nonpropagative laboratory procedures, and BSL-3 practices, containment equipment, and facilities are recommended for all other manipulations of known or potentially infectious materials. Recently, the World Health Organization (WHO) commissioned a revision of the current WHO Laboratory Biosafety Manual (LBM) using a risk-based approach for the fourth edition [55]. Using this approach, the LBM will suggest that only the most high-risk activities are required to be performed in laboratories with heightened control measures such as BSL-3 laboratory facilities.…”
Section: Discussionmentioning
confidence: 99%
“…Local risk assessments can allow for alternative ways of mitigating risk if a laboratory cannot fully integrate the recommendations of the ACG. The new version is fully in agreement with the recent rethinking of biosafety by the World Health Organization, which has been concerned that the perceived ''need'' for expensive containment facilities in resource-poor sites may hinder scientific and public health progress; the new WHO Laboratory Biosafety Manual emphasizes practices and procedures, not engineering controls (Kojima et al 2018).…”
mentioning
confidence: 75%
“…In a qualitative study conducted in Brazil to determine adherence to measures, participants reported that limited infrastructure was a contributing factor to their inability to adhere to good health practice [ 30 ]. In connection with the revised laboratory biosafety manual, “core requirements” have been proposed emphasizing laboratory infrastructure and other equipment [ 31 ]. Training programs like GIBACHT contribute to enhancing knowledge and skills in in-service professionals and bring out teams of trainers of trainers.…”
Section: Discussionmentioning
confidence: 99%